1994
DOI: 10.1007/bf02229206
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the reliability and validity of the personality assessment inventory

Abstract: The reliability, discriminant validity, and construct validity of the Personality Assessment Inventory (PAI) -a multidimensional self-report measure of abnormal personality traits-were examined within the Australian context. Subjects included 151 normal individuals, 30 alcoholics, and 30 schizophrenic patients. A subsample of 70 non-psychiatric adults responded to the PAI items twice over a test-retest interval of 28 days. The resulting median retest coefficient was 0. 7, indicating less than optimal stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 19 publications
1
36
1
5
Order By: Relevance
“…Morey's (1991) initial approach to evaluating its structure was to identify dimensions that accounted for the relations among all of the instrument's scales. Although some dimensions within the PAI exhibited good levels of replication in subsequent research (Morey, 2007), this was not the case for all of the dimensions, and some studies have reported inconsistent findings (e.g., Boyle & Lennon, 1994). Many, but not all, previous studies have been limited by relatively small and homogenous samples and the use of exploratory analytical approaches.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Morey's (1991) initial approach to evaluating its structure was to identify dimensions that accounted for the relations among all of the instrument's scales. Although some dimensions within the PAI exhibited good levels of replication in subsequent research (Morey, 2007), this was not the case for all of the dimensions, and some studies have reported inconsistent findings (e.g., Boyle & Lennon, 1994). Many, but not all, previous studies have been limited by relatively small and homogenous samples and the use of exploratory analytical approaches.…”
Section: Discussionmentioning
confidence: 84%
“…Replication of the other dimensions has not been as consistent as that for affective disruption and exploitive hostility. Additionally, research using both exploratory and confirmatory factor analytical techniques did not find support for a four-dimension structure of the PAI within an Australian sample of community-dwelling adults and patients diagnosed with alcohol dependence or schizophrenia (Boyle & Lennon, 1994; but see Morey, 1995).…”
mentioning
confidence: 98%
“…The Borderline Features (BOR) and Antisocial Features (ANT) Clinical scales were used in this study. The PAI has demonstrated good reliability and validity in census, college, and clinical samples (e.g., Boyle & Lennon, 1994;Kurtz et al, 1993;Morey, 1991;Walters, Duncan & Geyer, 2003 (3) Note. BPD = borderline personality disorder group; APD = antisocial personality disorder group.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…21 It has high internal consistency and test-related reliability. 22 For this study, questions in the PAI related to depression and anxiety were extracted.…”
Section: Personality Assessment Inventorymentioning
confidence: 99%